Functional Properties of Factor VIIa/Tissue Factor Formed with Purified Tissue Factor and with Tissue Factor Expressed on Cultured Endothelial Cells - Almus, Fanny E; Mohan Rao, L Vijaya; Rapaport, Samuel I (Thrombosis and Haemostasis, 1989)
Factor VIIa (F. VIIa)/tissue factor (TF) function was examined using purified human TF reconstituted into mixed phospholipid vesicles and TF expressed on cultured human umbilical vein endothelial cells (HUVEC) treated with thrombin. In reaction mixtures containing either type of TF, F. VIIa, 10 nM, either 3H-factor X or 3H-factor IX, 88 nM, and Ca2+, 5 mM, F. VIIa/TF activated factor X (F. X) several fold faster than it activated factor IX (F. IX). Adding heparin, 1 U/ml, increased rates of activation of both substrates and F. X remained the preferred substrate. Adding plasma at concentrations of 5%;or above inhibited factor VIIa/TF catalytic activity. Inhibition was shown to require F. Xa as a cofactor, was prevented by antibodies to extrinsic pathway inhibitor (EPI), and was reversible by decalcification. Thus, with factor VIIa/TF formed with both types of TF, EPI appeared responsible for inhibition induced by plasma. Our data indicate that functional properties of factor VIIa/TF as delineated in reaction mixtures made with purified TF reconstituted into mixed phospholipid vesicles also hold for factor VIIa/TF activity on the surface of cultured HUVEC.
Keywords: Tissue factor; Extrinsic pathway inhibitor; Heparin; Factor X and factor IX; Endothelial cells